The effect of mutant replication initiation proteins and antisense RNA to the gene on maize streak virus replication - Mangwende,Tichaona (Department of Molecular and Cell Biology, 2023)
Maize (Zea mays L) is a major crop plant belonging to the family Poaceae, which includes other important cereals such as wheat, rice, barley and oats (Kellogg, 1998). Other grass crops are rye, common millet, finger millet, teff, sugarcane and sorghum. Many of these are important food crops in most parts of the world, including Africa. The sustainable production of sufficient and affordable food for a rapidly increasing population is one of Africa's greatest challenges.